IMPACT OF CLIMATE CHANGE ON MARINE BIODIVERSITY AND FISHERIE - Donny Juliandri Prihadi; Shazia Akhtar; Zara Ali (Yayasan Adra Karima Hubbi, 2025)
Climate change poses significant threats to marine biodiversity and fisheries, impacting ecosystems and the livelihoods that depend on them. Rising sea temperatures, ocean acidification, and altered salinity levels are among the key environmental changes affecting marine life. Understanding these impacts is crucial for developing effective management strategies. This study aims to investigate the effects of climate change on marine biodiversity and the resulting implications for fisheries. The research seeks to identify vulnerable species and ecosystems, as well as assess the economic consequences for fishing communities. A comprehensive literature review was conducted, analyzing existing studies on climate change impacts on marine ecosystems. Data from various regions were synthesized to evaluate changes in species distribution, abundance, and community composition. Economic assessments of fisheries were incorporated to understand the socio-economic implications. Findings indicate significant shifts in marine biodiversity due to climate change, with some species migrating to cooler waters while others face population declines. These changes have direct implications for fisheries, leading to altered catch patterns and economic instability for fishing communities. Vulnerable species were identified, highlighting the need for targeted conservation efforts. This research underscores the urgent need for adaptive management strategies to mitigate the impacts of climate change on marine biodiversity and fisheries. Collaborative efforts between scientists, policymakers, and fishing communities are essential to ensure the sustainability of marine resources in the face of ongoing environmental changes.